A new bird track, Koreanaornis lii ichnosp. nov., from the Lower Cretaceous Hekou Group in the Lanzhou-Minhe Basin, Gansu, Northwest China, and implications for Early Cretaceous avian diversity. (November 2016) - Xing, Lida; Buckley, Lisa G.; Lockley, Martin G.; Zhang, Jianping; Marty, Daniel; Wang, Yan; Li, Jianjun; McCrea, Richard T.; Peng, Cuo
Abstract: There are a growing number of Early Cretaceous avian tracks and trackways from around the world, with Asia (China and Korea) having the largest reported number and diversity of Mesozoic avian traces to date, and these new discoveries are increasing the Early Cretaceous avian ichnodivesrity of Laurasia. Here we report on a new Lower Cretaceous avian track locality in the Guanshan area, Yongjing County, Gansu Province, northwest China, and on a novel ichnospecies of Koreanaornis, Koreanaornis lii ichnosp. nov. Koreananornis lii is distinct from other Koreanaornipodidae in that it possesses a consistently wider digit divarication than previously described tridactyl tracks, and possess a short, small, posteromedially oriented hallux that displays a different orientation than that seen in Koreanaornis hamanensis . The lack of linear and angular data reported for digit I traces of many avian ichnotaxa has the potential to give misleading results in multivariate statistical analyses. Also, the wide divarication of Koreanaornis lii causes the ichnotaxon to not group with other Koreanornipodidae in multivariate analyses, but with Ignotornidae. Despite the results of the analyses, K. lii is morphologically distinct from these ichnotaxa. The results demonstrate that relying solely on multivariate statistical analyses without careful examination of footprint morphology will result in erroneous ichnospecies groupings. While new vertebrate ichnotaxa discoveries from Asia may support the hypotheses of the presence of a unique and endemic Asian vertebrate ichnofauna during the Cretaceous, the recent discovery of skeletal remains interpreted to be of a volant wading bird from the Early Cretaceous, and recent reports of tracks from volant avians, could suggest that flighted avians of the shore- and wading bird ecotypes could have had a Laurasian-wide distribution during the Early Cretaceous. However, strong convergence in foot morphology of shore- and wading birds suggests that avian ichnotaxa found in both present-day Asia and North America may have been made by birds endemic to eastern and western Laurasia during the Early Cretaceous.